GAMBARAN TINGKAT PENGETAHUAN IBU HAMIL TERHADAP KEJADIAN ANEMIA DI PUSKESMAS KALUKU BODOA KOTA MAKASSAR TAHUN 2024 - Munawwarah. M, St.; Harun, Ayatullah; Hartini, Noviyani; Destriana, Airin (JURNAL KESEHATAN DELIMA PELAMONIA, 2024)
Background: Pregnancy is the process of fusion between sperm and egg cells, followed by implantation. Anemia is a common problem during pregnancy. Therefore, it is important for pregnant women to understand anemia so they can take appropriate steps and face this condition with a positive attitude. This involves regular check-ups by a midwife. The purpose of this study was to determine the significance of the level of knowledge of pregnant women about anemia at the Kaluku Bodoa Community Health Center. This study used an observational design with a descriptive approach, with a population of 128 pregnant women and a sample of 30 pregnant women using accidental sampling. Results and Conclusions: Based on the results of the study at the Kaluku Bodoa Community Health Center, it was shown that 83.3% of pregnant women had good knowledge about anemia, while 16.7% had poor knowledge.